TELAAH TERHADAP PROBLEM PEMBELAJARAN DI UNIVERSITAS MUHAMMADIYAH SURAKARTA PADA TAHUN 2013-2014 - Aly, Abdullah (Muhammadiyah University Press, 2014)
In the beginning of 56th anniversary, Universitas Muhammadiyah Surakarta(UMS) still needs to improve and develop the implementation of Tri Dharma PerguruanTinggi (three functions of higher education institutions in Indonesia). To improve anddevelop its functions above, this study aims at exploring more detail in line with thelearning problems conducting in UMS for the academic year of 2013-2014. Based onthe bibliographic-descriptive study through the available documents analysis, the findingof this research shows that the main learning problem in UMS is the lecturers have notapplied the Student Centered Learning (SCL) learning model totally. Most of the lecturersstill apply the learning model based on Teacher Centered Learning (TCL). Few of themwho have applied learning model based on SCL. This main problem may cause threenew next problems of learning in UMS, they are: (1) the learning tends to be behavioristicand not constructive, (2) the learning is more stressing on the pedagogical aspect andnot andragogy, finally; (3) the learning have not involved the studentsâ activenesscomprehensively.Key Words: constructivism; behaviorism; pedagogy and andragogy.Memasuki usianya ke-56, UMS masih harus melakukan perbaikan danpengembangan dalam pelaksanaan tri dharma perguruan tinggi. Untuk kepentinganperbaikan dan pengembangan tersebut, studi ini dilakukan dengan tujuan untukmenggali lebih jauh problem-problem pembelajaran yang berlangsung di UMS selamatahun 2013-2014. Berdasarkan studi deskriptif-bibliogratif melalui telaah dokumenyang tersedia, studi ini menemukan problem utama pembelajaran di UMS, yaitu bahwapara dosen belum sepenuhnya menerapkan model pembelajaran berbasis SCL (StudentCentered Learning). Sebagian besar dosen masih menerapkan model pembelajaranberbasis TCL (Teacher Centered Learning). Sebagian kecil dosen UMS lainnya barumulai menerapkan model pembelajaran berbasis SCL. Problem utama tersebutselanjutnya menyebabkan tiga problem turunan dalam pembelajaran di UMS, yaitu:(1) pembelajaran cenderung bersifat behavioristik dan bukan konstruktivistik, (2)pembelajaran lebih menekankan pada aspek pedagogis dan bukan andragogis, dan (3)pembelajaran belum sepenuhnya melibatkan keaktifan para mahasiswa.Kata Kunci: konstruktivisme; behaviorisme; pedagogi andragogi